Virtual inertia based hierarchical control scheme for distributed generations considering communication delay - Zhou, Chang; Liao, Yingqi; Zhang, Kaifeng; Xu, Xiaohui; Liao, Jiaqi (Frontiers in Energy Research, 2023)
The virtual inertia technology of DGs (Distributed Generations) can provide inertia and damping support for the power system by imitating the traditional synchronous machine. However, the inherent delay problems aroud the comunication and process links of the virtual inertia control will make an impact on the fast support effect. In this paper, the virtual inertia based hierarchical control scheme considering communication delay for DGs integration systems is proposed. The hierarchical control architecture including the PQ primary control and the virtual inertia based secondary control method which can realize the optimal power utilization and certain frequency support under the situation of communication signal delay at the same time. Firstly, the basic hierarchical control scheme for DGs and corresponding small signal modeling considering communication delay are presented. Then to enhance the inertia support ability of the DG integration system, an improved hierarchical control strategy considering communication delay is designed based on the robust passivity method to compensate the equivalent delay disturbance. Finally, the effectiveness verification of the proposed control is carried out with the simulation cases in PSCAD platform.